Look at me when I talk to you : EAL learners in non-EAL classrooms - Helmer, Sylvia (Pippin teacher's library, 2012)
Culture is communication and communication is culture. But communicating involves much more than just memorizing vocabulary and learning grammar rules. As we welcome into our classrooms ever increasing numbers of students from around the globe whose first language is not English, we need a heightened sensitivity to those cultural issues affecting the way people interact with one another. In this third edition of Look at Me When I Talk to You, Sylvia Helmer and Catherine Eddy continue to explore the underlying fundamentals of communication to show how culture influences the messages sent? and received. Elements of both the theory and practice of communicating in a multicultural setting are discussed, with examples from real classrooms to illustrate the issues that can, and do, arise. Now fully revised and updated, with a greatly expanded bibliography, all chapters conclude with a set of discussion questions to further extend thinking and learning, tailor made for thoughtful review. An entirely new chapter has been added, addressing the needs of the growing number of EAL leaners facing additional learning challenges. The final chapter spotlights many of the questions on teachers? minds about optimizing support for EAL learners? successful integration. The practical suggestions and strategies for helping students cope in their new culture make this book a must-read for all teachers working with those students who are learning English as an Additional Language in the classrooms of today. Its key message may be summed up as?Take nothing for granted.? Or, as we often remind ourselves,?Assume nothing!? Cultural norms accepted in much of the English-speaking world are not necessarily a reliable measure when interpreting the actions of others, or for assuming that our own actions will be well understood, and nor can they be used to predict what will happen in a given situation. As teachers, we need to transcend our own subconscious cultural training and.